2018
DOI: 10.3389/fonc.2018.00438
|View full text |Cite
|
Sign up to set email alerts
|

Development and Internal Validation of Novel Nomograms Based on Benign Prostatic Obstruction-Related Parameters to Predict the Risk of Prostate Cancer at First Prostate Biopsy

Abstract: The present study aimed to determine the ability of novel nomograms based onto readily-available clinical parameters, like those related to benign prostatic obstruction (BPO), in predicting the outcome of first prostate biopsy (PBx). To do so, we analyzed our Internal Review Board-approved prospectively-maintained PBx database. Patients with PSA>20 ng/ml were excluded because of their high risk of harboring prostate cancer (PCa). A total of 2577 were found to be eligible for study analyses. The ability of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Such an approach binds the decision to perform biopsy to the clinical suspicion of PCa to be determined using MRI, risk calculators, and biomarkers [1]. While several risk calculators and biomarkers have been developed and are currently under evaluation [2][3][4], the "MRI pathway" is supported by level 1 evidence, but seems to be limited by the low to moderate inter-reader and -center reproducibility and the low specificity/positive predictive value (PPV) [5][6][7]. Studies have shown that omitting biopsies in patients with no lesion on MRI would miss up to 5-11% of all csPCa cases (ISUP grade >2) [5,8], whereas performing biopsy in all patients with an equivocal MRI finding (PI-RADS 3 lesions considered to be positive by guidelines [9]) can result in a diagnosis of csPCa in 3-50% of the patients [5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach binds the decision to perform biopsy to the clinical suspicion of PCa to be determined using MRI, risk calculators, and biomarkers [1]. While several risk calculators and biomarkers have been developed and are currently under evaluation [2][3][4], the "MRI pathway" is supported by level 1 evidence, but seems to be limited by the low to moderate inter-reader and -center reproducibility and the low specificity/positive predictive value (PPV) [5][6][7]. Studies have shown that omitting biopsies in patients with no lesion on MRI would miss up to 5-11% of all csPCa cases (ISUP grade >2) [5,8], whereas performing biopsy in all patients with an equivocal MRI finding (PI-RADS 3 lesions considered to be positive by guidelines [9]) can result in a diagnosis of csPCa in 3-50% of the patients [5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors can be used to build mathematical models for the prediction and diagnosis of PCa, such as age, pentraxin 3, prostate-specific antigen, absence of bladder outlet obstruction, etc. [ 2 , 3 ] While sleep is very important for physical and mental health. [ 4 ] Sleep duration, quality of sleep, and so on might be related to the development of some diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A dozen of nomograms for prediction of PCa and/or clinically significant prostate cancer (CSPCa) with Gleason score (GS) ≥3+4 had been developed in Western countries (6)(7)(8)(9). Researchers found that the models derived from Western populations overestimated the predicated risk of PCa and CSPCa among the East Asian populations, mainly due to the racial differences between two populations (10,11).…”
Section: Introductionmentioning
confidence: 99%